2019
DOI: 10.1186/s12916-019-1461-z
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention and depression apps’ suicide risk assessment and management: a systematic assessment of adherence to clinical guidelines

Abstract: BackgroundThere are an estimated 800,000 suicides per year globally, and approximately 16,000,000 suicide attempts. Mobile apps may help address the unmet needs of people at risk. We assessed adherence of suicide prevention advice in depression management and suicide prevention apps to six evidence-based clinical guideline recommendations: mood and suicidal thought tracking, safety plan development, recommendation of activities to deter suicidal thoughts, information and education, access to support networks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 45 publications
(48 reference statements)
4
86
1
1
Order By: Relevance
“…Use of digital assessment tools would help patients to report and collect symptoms' severity data at their peak. However, currently available apps often lack clinical reliability requirements [43].…”
Section: Discussionmentioning
confidence: 99%
“…Use of digital assessment tools would help patients to report and collect symptoms' severity data at their peak. However, currently available apps often lack clinical reliability requirements [43].…”
Section: Discussionmentioning
confidence: 99%
“…A failure to treat depression adequately effects patients both mentally and physically. [ 1 , 2 ] Antidepressants are commonly used in clinic based on the monogramming neurotransmitter hypothesis of depression. Aside from the long-lasting beneficial effects, antidepressants may cause clear unfavorable responses and side effects.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of standalone mental health apps investigated published literature on randomized controlled trials of mental health apps and found such small effect sizes that the authors could not recommend standalone psychological interventions at all 29 . Most concerning, a study of 69 apps for depression found six apps, downloaded more than two million times, provided inaccurate or non-existent suicide crisis helpline phone numbers 30 —underscoring the importance of ensuring apps actually do what they claim as a simple but critical bar for evaluation. These examples reveal that beneficence is not necessarily the norm when it comes to claims of app effectiveness, underscoring the need for a thorough, comprehensive system for evaluation.…”
Section: A Pyramid Process: Components Of the Frameworkmentioning
confidence: 99%